An efficient electrochemical sensor based on three-dimensionally interconnected mesoporous graphene framework for simultaneous determination of Cd(II) and Pb(II). (20th December 2016) - Xiao, Lili; Wang, Biwei; Ji, Li; Wang, Fu; Yuan, Qunhui; Hu, Guangzhi; Dong, Angang; Gan, Wei
Abstract: Recently, ordered mesoporous carbon has displayed attractive performance in electrochemical catalysis and sensing, benefiting from its rich and tunable pore texture. In this work, a novel electrochemical sensor based on a three-dimensionally interconnected mesoporous graphene framework (MGF) was developed for simultaneous determination of Cd(II) and Pb(II) in aqueous solution. Attributable to the abundant three-dimensional mesopores and good electrical conductivity of MGF, as well as the synergistic effect of Nafion and in-situ plated bismuth films, a highly sensitive determination of mixed metals at a Bi/MGF-Nafion/GCE is achieved. The proposed sensor exhibits wide linear responses for Cd(II) and Pb(II), ranging from 2–70 μg L −1 and 0.5–110 μg L −1, respectively. The detection limits are about 0.5 and 0.1 μg L −1 for Cd(II) and Pb(II), respectively, which are about 6 and 100 times lower than the drinking water standards set by the World Health Organization (WHO). Moreover, Bi/MGF-Nafion/GCE has been applied for the detection of mixed metals in real water samples. The satisfying recoveries (87.5-109.2%) and relative standard deviations (RSD, 3.7-8.6%) make the proposed electrode a promising candidate for rapid and on-site monitoring of environmental metallic pollutants.